Тихий Дон: [роман] (Михаил Шолохов) - Шолохов Михаил Александрович (Азбука-классика, 2018)
Экземпляры: СБ (20190226) / Инвентарный номер: 57277 / Цена: 150.00 / Сис.шифр: Р2 / Авт.знак: Ш 78 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6